Tuning in on the Becoming of Music - Østergaard Edvin (De Gruyter, 2021)
In this article, I explore the music-in-becoming as a dialogue. The thesis of my inquiry is that during musical composition, the composer’s listening is marked by both activeness and receptiveness; actively structuring the sounding work, and receptively letting the work express itself as it takes its form. Composer and work merge in sudden moments of attunement, the sensation of coherence between the so-fare completed and the anticipation of the as-of-yet unformed work. Composition is all about balancing writing as a handicraft with those rare, unexpected moments of attunement. I discuss the emerging work’s invitational character and the fact that during composition, the piece seems to request the composer’s attention. The audibility of the work’s voice depends on the composer’s ability to listen. Finally, the methodological considerations concerning sonic-artistic research show that researching sonic experiences requires competencies of being attentive, responsive, and reflective. Attentiveness is related to thorough listening experiences of the emerging music, responsiveness appears as a vital skill in a composer’s dialoguing with the music-in-becoming, and reflectiveness is associated with empirically documenting the processes. At the heart of this sonic research project, I place my lived experience of composing and the intimate relation between sound and listening.